Notodonta valeria, a new species (Lepidoptera, Notodontidae) from China, with taxonomic remarks on Notodonta ziczac (Linnaeus, 1758) - Saldaitis, Aidas; Ivinskis, Povilas; Rimsaite, Jolanta (Zootaxa, 2013)
A new species of Notodonta Ochsenheimer, 1810, N. valeria sp. n., from the Chinese Sichuan and Qinghai provinces is described. The new species differs in appearance, genitalia and DNA from its closest known relatives, Notodonta ziczac (Linnaeus) and Notodonta derbendica Daniel, 1965 stat. n. described from Europe and Iran, respectively. The genus Notodonta in the Palearctic is distributed in North Africa, Europe, Middle Asia, Russia (including Siberia), Japan, Korea and China. Three of the known 13 species are found in North America (Schintlmeister 2008). Sampling was conducted using UV lights and DNA barcodes (658 base pairs of Cytochrome Oxidase Subunit I 5' region, COI-5P) were prepared by Hebert's laboratory at the University of Guelph. Male and female genitalia dissections following Lafontaine (2004) were mounted in euparal, and a Wild M3Z microscope and Canon EOS 350D camera were used to prepare images. Taxonomic information and nomenclature follows Daniel 1965, Schintlmeister & Fang 2001, Schintlmeister 2008, Wu & Fang 2001. Acronyms used below: AFM = Alessandro Floriani (Milan, Italy); MNHU = Museum für Naturkunde der Humboldt Universität zu Berlin; MWM/ZSM = Museum Thomas Witt (Munich, Germany) /Zoologische Staatssammlung, Munich (Germany); NRCV = Nature Research Centre (Vilnius, Lithuania); OPB = Oleg Pekarsky (Budapest,Hungary); PMM = Pavel Morozov (Moscow, Russia).